2021
DOI: 10.1055/s-0041-1728832
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Antiphospholipid Antibodies: Time for a Reality Check?

Abstract: Antiphospholipid antibodies (aPL) comprise a panel of autoantibodies that reflect a potential prothrombotic risk in several autoimmune conditions, most notably antiphospholipid (antibody) syndrome (APS). aPL can be divided into those that form part of the laboratory criteria for APS, namely, lupus anticoagulant (LA), as well as anticardiolipin antibodies (aCL) and anti-β2-glycoprotein I antibodies (aβ2GPI) of the immunoglobulin G and M classes, and those that form a group considered as “noncriteria antibodies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 79 publications
1
41
0
4
Order By: Relevance
“…In this study, LAC was not tested. Finally, in a narrative review, Favarolo et al (16) found a median incidence of reported cases positive for aPL of 33% (with an interquartilic range of 11% to 52%).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, LAC was not tested. Finally, in a narrative review, Favarolo et al (16) found a median incidence of reported cases positive for aPL of 33% (with an interquartilic range of 11% to 52%).…”
Section: Discussionmentioning
confidence: 99%
“…[73][74][75] A role for lupus anticoagulant and antiphospholipid antibodies has been suggested for pathogenesis of COVID-19-associated coagulopathy. 52,[76][77][78][79][80] In severely infected patients, immobility under conditions of quarantine or hospitalization is another predisposing factor of thrombosis. 81,82 Modification of the equilibrium between clot formation and degradation in favor of hypercoagulability and hypofibrinolysis, impaired endothelial function, platelet hyperactivation, and excessive immune response are emerging as major contributors to the thrombotic complications.…”
Section: Pathophysiology Of Covid-19-associated Coagulopathymentioning
confidence: 99%
“…Primarily antinuclear antibody (ANA) and antibodies against elements of the coagulation cascade, such as antiphospholipid (APLA), anti-prothrombin and anti-heparin antibodies have been described. However, anti-citrullinated protein (ACPA), anti-neutrophil cytoplasmic antigen (ANCA), anti-SS-A/Ro antibodies and rheumatoid factor production has also been described with SARS-CoV-2 infection (12,(36)(37)(38). Some studies have also analysed histological changes induced by SARS-CoV-2 infection.…”
Section: Sars-cov-2 Infection Autoimmunity and Autoimmune Diseasesmentioning
confidence: 99%